2016
DOI: 10.1158/0008-5472.can-16-0544
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 2B Receptor Expression on Cancer Cells Promotes Metastasis

Abstract: Adenosine plays an important role in inflammation and tumor development, progression, and responses to therapy. We show that an adenosine 2B receptor inhibitor (A2BRi) decreases both experimental and spontaneous metastasis and combines with chemotherapy or immune checkpoint inhibitors in mouse models of melanoma and triple-negative breast cancer (TNBC) metastasis. Decreased metastasis upon A2BR inhibition is independent of host A2BR and lymphocytes and myeloid cells. Knockdown of A2BR on mouse and human cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 50 publications
5
147
1
1
Order By: Relevance
“…[57] Here the authors show that blockade of A 2B receptor in A 2B receptor deficient mice is able to reduce the metastasis of human triple negative breast cancer (TNBC) xenografts, confirming the critical role of A 2B receptor on cancer cells rather than host cells. [57] Altogether these preclinical studies strongly support the therapeutic potential of targeting adenosine in cancer.…”
Section: Critical Roles Of Adenosine In Tumor Progressionmentioning
confidence: 66%
See 4 more Smart Citations
“…[57] Here the authors show that blockade of A 2B receptor in A 2B receptor deficient mice is able to reduce the metastasis of human triple negative breast cancer (TNBC) xenografts, confirming the critical role of A 2B receptor on cancer cells rather than host cells. [57] Altogether these preclinical studies strongly support the therapeutic potential of targeting adenosine in cancer.…”
Section: Critical Roles Of Adenosine In Tumor Progressionmentioning
confidence: 66%
“…[116] In a recent paper it has been demonstrated that high expression of A 2B receptor is associated with poor survival in triple negative breast cancer (TNBC) patients. [57] As mentioned above, these authors demonstrate that A 2B receptor antagonist prevents metastasis of A 2B receptor-expressing tumor cells and improves survival when administered in combination with chemotherapeutic agents and immune checkpoints inhibitors monoclonal antibodies in both experimental and spontaneous murine models of metastasis. [57] The anti-metastatic effects of A 2B receptor antagonists is independent on lymphocytes and myeloid cells, whilst tumor A 2B receptor is critical.…”
Section: A 2b Receptor and Tumor Stromamentioning
confidence: 71%
See 3 more Smart Citations